Diversity of Cultural Tourism Attractions in Nairobi Urban Destination - Mwangi, Muhoro Grieveesbon; Wishitemi, Bob; Okello, Moses M (Journal of Tourism Management Research, 2020)
The purpose of this research was to find out the diversity of potential cultural attractions in Nairobi urban tourism destination. Today cities are tapping into diverse sources to increase international visitor arrivals as well as their spending. Cultural tourism and urban entertainment are the greatest motivation for urban tourism since culture is a fundamental component within the tourism system. The subjects of interest in this study for quantitative data consisted of foreign departing tourists through Kenya’s biggest airport - Jomo Kenyatta International Airport (JKIA) located in Nairobi. To get a complete picture of the research, the study also employed qualitative approach, specifically; in-depth interviews with public and private sector stakeholders to answer questions on key areas. The research found out there was a weak motivation to cultural attractions despite their proximity to the CBD. Thus, Nairobi urban cultural tourism destination managers should ensure that urban cultural attractions have the highest score if a definite visitor appeal is to be created, realized, and maintained for continued and repeat visitor visitation. The findings of this research have provided invaluable understanding on the opportunities available to cultural attractions available in Nairobi. This information can be used by private and public stakeholders to develop clear policies and collaborations on urban cultural tourism development.